The Correlation Between the Students’ Reading Habits and Motivation Toward Their Reading Comprehension at the Eighth Grade of SMPN 13 Mataram - Abdullah Jundi; Lalu Thohir; Agus Saputra; Lalu Nurtaat (Mataram University, 2024)
The objective of this study was to investigate the correlation between students' reading habits and motivation toward their reading comprehension at SMPN 13 Mataram, specifically among eighth-grade students. The number of samples were 32 participants at the eighth grade SMPN 13 Mataram selected using cluster sampling. This study was conducted using a quantitative method and a correlational research design by using product-moment coefficient correlation analysis. The research employed a correlational method, utilizing questionnaires and tests as data collection tools implemented with IBM SPSS 27. The findings revealed significant correlations between reading habits, reading motivation toward their reading comprehension among eighth-grade students at SMPN 13 Mataram. The statistical analysis shows the following correlation coefficients: Reading habits and reading comprehension: 0.118, with a significance value less than 0.05. Reading motivation and reading comprehension:0.99, with a significance value less than 0.05. Reading habits and reading motivation toward their reading comprehension: 0.037, with a significance value less than 0.05. Since all correlations are statistically significant (p < 0.05), the alternate hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected. This indicates that there are significant correlations between reading habits, reading motivation, and reading comprehension. Keywords: A correlation, reading habits, reading motivation, reading comprehension, eighth-grade students.